Complete Chloroplast Genome Variants Reveal Discrete Long-Distance Dispersal Routes of Rhizophora in the Western Indian Ocean - Triest, Ludwig; Sierens, Tim; Van der Stocken, Tom (Frontiers in Conservation Science, 2021)
Historical processes of long-distance migration and ocean-wide expansion feature the global biogeographic pattern of Rhizophora species. Throughout the Indian Ocean, R. stylosa and R. mucronata appear as a young phylogenetic group with expansion of R. mucronata towards the Western Indian Ocean (WIO) driven by the South Equatorial Current. Nuclear microsatellites revealed genetic patterns and breaks, however, estimating propagule dispersal routes requires maternally inherited cytoplasmic markers. Here, we examine the phylogeography of 21 R. mucronata provenances across a >4,200 km coastal stretch in the WIO using R. stylosa as outgroup. Full length chloroplast genome (164,474 bp) and nuclear ribosomal RNA cistron (8,033 bp) sequences were assembled. Boundaries, junction point, sequence orientation and stretch between LSC/IRb/SSC/IRa/LSC showed no differences with the R. stylosa chloroplast genome. A total of 58 mutations in R. mucronata encompassing transitions/transversions, insertion-deletions and mononucleotide repeats revealed three major haplogroups. Haplonetwork, Bayesian ML and Approximate Bayesian Computation (ABC) analyses supported discrete historical migration events. An ancient haplogroup A in the Seychelles and eastern Madagascar was as divergent from other R. mucronata haplogroups as it was from R. stylosa. A star-like haplonetwork referred to recent range expansion of haplogroup B from northern Madagascar towards the African mainland coastline, including a single variant spanning >1,800 km across the Mozambique Channel Area. Populations south of Delagoa Bight contained haplogroup C and originate from a unique bottleneck dispersal event. Divergence estimates of pre- and post-Last Glacial Maximum illustrated a recent emergence of WIO Rhizophora mangroves compared to other oceans. Connectivity patterns could be aligned with directionality of major ocean currents. Madagascar and the Seychelles each harbored haplogroups A and B, albeit among spatially separated populations, explained from a different migration era. Likewise, the Aldabra Atoll harbored spatially distinct haplotypes. Nuclear ribosomal cistron (8,033bp) variants corresponded to haplogroups and confirmed admixtures in the Seychelles and Aldabra. These findings shed new light on the origins and dispersal routes of R. mucronata lineages that have shaped their contemporary populations in large regions of the WIO, which may be important information for defining marine conservation units, both at ocean scale and at level of small islands.